2014
DOI: 10.1007/s00259-014-2726-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined SPECT/CT improves detection of initial bone invasion and determination of resection margins in squamous cell carcinoma of the head and neck compared to conventional imaging modalities

Abstract: Hybrid SPECT/CT has a high specificity as it can provide additional information about the existence and local extent of malignant bone infiltration of the mandible. Although the sensitivity of conventional SPECT is similar to that of SPECT/CT, the latter provides a much better delineation of the local tumour-bone contact area. Based on this information, surgical intervention of the rim versus partial resection can be planned and performed more precisely. Patient outcome can be improved by avoiding undertreatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 51 publications
1
19
0
1
Order By: Relevance
“…Kolk et al posit that the combination of CT/ SPECT can improve sensitivity and specificity of detecting bony disease, ultimately decreasing false negative and false positive findings that can be associated with conventional CT and MRI imaging. 12 Indeed, a systematic review by Uribe et al 13 in 2013 looked at 5 studies and 130 tumors and concluded that CT and MRI demonstrated the greatest sensitivity (94% and 91%, respectively) and specificity (100%) in detecting mandibular invasion compared with CBCT (83% and 97%, respectively) PET/CT (53% and 97%, respectively), and panoramic X-ray (55% and 92%, respectively). Other studies demonstrate that an MRI and a bone scan can overestimate mandibular involvement (with more false-positive results), and that CT, panorex, and clinical examination are the optimal means by which to assess bone invasion.…”
Section: Bone Invasionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kolk et al posit that the combination of CT/ SPECT can improve sensitivity and specificity of detecting bony disease, ultimately decreasing false negative and false positive findings that can be associated with conventional CT and MRI imaging. 12 Indeed, a systematic review by Uribe et al 13 in 2013 looked at 5 studies and 130 tumors and concluded that CT and MRI demonstrated the greatest sensitivity (94% and 91%, respectively) and specificity (100%) in detecting mandibular invasion compared with CBCT (83% and 97%, respectively) PET/CT (53% and 97%, respectively), and panoramic X-ray (55% and 92%, respectively). Other studies demonstrate that an MRI and a bone scan can overestimate mandibular involvement (with more false-positive results), and that CT, panorex, and clinical examination are the optimal means by which to assess bone invasion.…”
Section: Bone Invasionmentioning
confidence: 99%
“…Other studies demonstrate that an MRI and a bone scan can overestimate mandibular involvement (with more false-positive results), and that CT, panorex, and clinical examination are the optimal means by which to assess bone invasion. 3,12,14,15 Sarri on P erez et al 6 examined 19 studies comparing Xray, CT, MRI, and PET in assessing bone invasion of the mandible. The authors concluded that, although controversial due to conflicting results, nonstandardized definitions of mandibular invasion, and heterogeneous patient populations, current evidence supports the use of CT and MRI in the assessment of bone invasion.…”
Section: Bone Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…This case illustrates detection of bone invasion earlier with bone scintiscan than on PR study, the accuracy of bone scinitigraphy was 100% (36 of 36 patients) in determining the full extent of tumor involvement in jaw bones [34]. Some studies found that combination of real and rear time imaging was more precise over single modality [6,11,13,19,32,35]. Sensitivity and NPV obtained by us were 100% with Tc scan when used either alone or in Tc scan/PR compared to PR alone (69.2%, 55.5%).…”
Section: Discussionmentioning
confidence: 98%
“…It has been found that MRI is better at evaluating the extent of soft tissue invasion as well as medullary cavity invasion, whereas CT is better at determining cortical disruption . Nuclear medicine techniques such as PET and SPECT can be fused with CT scans in order to provide both metabolic and anatomic information within the same scan . However, even these imaging modalities are currently unable to precisely determine the extent of cortical and medullary bone invasion .…”
Section: Discussionmentioning
confidence: 99%